2021
DOI: 10.1093/jnci/djab023
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity With Breast Cancer Outcome in Relation to Cancer Subtypes: A Meta-Analysis

Abstract: Background Obesity at breast cancer (BC) diagnosis has been associated with poor outcome, although the magnitude of effect in different BC subtypes is uncertain. We report on the association of obesity/overweight at diagnosis of non-metastatic BC with disease-free (DFS) and overall survival (OS) in the following defined subtypes: hormone receptor positive/HER2 negative (HR+HER2-), HER2 positive (HER2+), and triple negative (TNBC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 42 publications
1
48
2
Order By: Relevance
“…However, this needs to be further addressed in future studies and the results from Ballinger et al, should be interpreted with caution as they are limited by the small population of 172 chemoresistant TNBC patients with residual disease and the short follow-up time (primary endpoint is two year DFS). Furthermore, in a recent metaanalysis evaluating all breast cancer subtypes, obesity (BMI ≥ 30 kg/m 2 ), however not overweight (BMI 25-30 kg/m 2 ), was reported to influence prognosis in TNBC patients 43 . Compared to this meta-analysis, the partly different results by Lohmann, et al, may be explained by their inclusion of observational studies with heterogeneous BMI comparator groups, heterogeneous endpoints and interventional cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, this needs to be further addressed in future studies and the results from Ballinger et al, should be interpreted with caution as they are limited by the small population of 172 chemoresistant TNBC patients with residual disease and the short follow-up time (primary endpoint is two year DFS). Furthermore, in a recent metaanalysis evaluating all breast cancer subtypes, obesity (BMI ≥ 30 kg/m 2 ), however not overweight (BMI 25-30 kg/m 2 ), was reported to influence prognosis in TNBC patients 43 . Compared to this meta-analysis, the partly different results by Lohmann, et al, may be explained by their inclusion of observational studies with heterogeneous BMI comparator groups, heterogeneous endpoints and interventional cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence tends to be stronger for hormone receptor + breast cancer, a recent metaanalysis found that obesity was associated with worse diseasefree survival and overall survival for all subtypes, including HER2 + and triple-negative breast cancer. 51 The effect of central adiposity, measured as waist-to-hip ratio or waist circumference, on breast cancer mortality has received little attention, but a meta-analysis based on four studies found elevated mortality for those with high waist-to-hip ratio. 11 Weight changes after diagnosis are particularly important among survivors.…”
Section: Obesity and Female Breast Cancer Risk: Current Evidencementioning
confidence: 99%
“…These data suggest that precision medicine approaches to neoadjuvant treatment are of pressing importance. Indeed, a recent meta-analysis hinted at a differing effect of obesity on outcomes based on cancer subtype: Lohmann and colleagues observed a larger magnitude of the deleterious effect of excess body weight in triple-negative and hormone receptor-positive, HER2-negative breast cancer as compared to hormone receptorpositive, HER2-positive breast cancer (39). However, these data stop short of suggesting specific breast cancer driver mutations that may be more or less responsive to therapies aiming to reduce circulating insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%